If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4a + -7) + a = 76 Reorder the terms: 2(-7 + 4a) + a = 76 (-7 * 2 + 4a * 2) + a = 76 (-14 + 8a) + a = 76 Combine like terms: 8a + a = 9a -14 + 9a = 76 Solving -14 + 9a = 76 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 9a = 76 + 14 Combine like terms: -14 + 14 = 0 0 + 9a = 76 + 14 9a = 76 + 14 Combine like terms: 76 + 14 = 90 9a = 90 Divide each side by '9'. a = 10 Simplifying a = 10
| -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 | | -4+4x=-8 | | 2((x+2)+(x+3))=16 | | n+6=19 |